Interleukins 20 and 8 – less widely known cytokines in psoriasis - Kutwin, Magdalena; Woźniacka, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Psoriasis is a common immune-mediated inflammatory dermatosis affecting 2–3% of the northern European population. Although its aetiology is not completely elucidated, it is widely accepted that activated immune cells and keratinocytes stimulate keratinocyte hyperproliferation by production of cytokines; indeed, elevated amounts of pro-inflammatory cytokines have been observed in skin lesions and patient serum. By identifying those playing a central role in the disease pathogenesis, it will be possible to indicate a potential therapeutic target. Drugs targeting tumour necrosis factor (TNF-), interleukin (IL)-12/23, IL-17, IL-22 and IL-23 and Janus kinase inhibitors have been found to successfully alleviate resistant skin lesions. However, psoriasis is a complex disease with varied cellular interactions and cytokines, and a complex receptor network. Therefore, this review paper examines the less widely known cytokines IL-20 and IL-8, their therapeutic potential and their role in skin lesion development. Although promising results have been obtained for IL-20 and IL-8 treatment, and their role in the psoriasis skin lesion development is well documented, the role of these two cytokines remains overshadowed by that of the wider systemic cytokine storm.